Taking the Concept of Citizenship in Mental Health across Countries. Reflections on Transferring Principles and Practice to Different Sociocultural Contexts - Eiroa-Orosa, Francisco José; Rowe, Michael (Frontiers in Psychology, 2017)
Transferring principles and practices to different sociocultural and professional contexts in the field of mental health can be very complex. Previous research on public health policy points to difficulties in different areas such as the understanding the new concepts, their applicability in different health systems, and suitable approaches to its effective implementation. The purpose of this article is to describe and analyze the process of transferring the concept of Citizenship, from its U.S. origins in mental health outreach work with persons who are homeless to Catalonia, Spain. We define Citizenship as promoting the rights, responsibilities, roles, resources and relationships of persons with mental illnesses, along with a sense of belonging that is validated by other citizens. The process of this transition involves embedding Citizenship in the mental health “first-person” (internationally known as Consumer/Survivor/Peer) movement in Catalonia. The paper includes a discussion of the concept of transference, including a case example of the adoption of the concept of mental health recovery in different countries. Following this, we describe the U.S. Citizenship model and key elements of its development. We then turn to Spain and the evolution of its mental health system, and then to Catalonia for a brief case history of transference of the principles and practices of Citizenship to that region. The “take home message” of this work is that concepts being brought from one sociocultural and national context to another must focus on contextualization in the ‘adoptee’s’ practices, including the balance between personal involvement and professional rigor, the involvement of key actors, and ongoing evaluation of actions taken.